Theme for a dream - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Making money out of essential oils extracted from plants is like taking a magical mystery tour. ACP growers and producers need to meet a lot of conditions, but success can be sweet. How would you like your ylang-ylang oil? Steamed or squeezed or...